Education in public health major at Polish medical universities in the aspect of the Bologna Process - Stelmach, Włodzimierz; Bąk-Walczak, Ewa; Zawadzka, Magdalena; Kowalska, Alina; Bryła, Marek (Polish Journal of Public Health, 2012)
Introduction. This article is a continuation of a review paper called “Bologna Process and education towards public health in Poland”. The Bologna Process is still evolving. Since 2007 two consecutive meetings have taken place: in Leuven/Louvain-la-Neuve, Belgium on 28-29 April 2009 and in Budapest/Vienna on 11-12 March 2010. Aim. The aim of the work is to analyze the education of students of medical universities (medical academies) towards public health in 2000-2009 in Poland in the light of the Bologna Process guidelines. Material and methods. Eleven universities were included in the study, all of which had public health majors introduced. The research was carried out from July 2009 to July 2010 using a specially designed survey. Despite numerous reminders, only 8 universities sent back their responses. The results were analyzed descriptively and presented in the form of tables and figures. The values of the analyzed parameters, measured in the nominal scale, were characterized using structure indices. Results. In the light of the conducted study, it turned out that in Poland till 2007 there had been a dynamic development in education towards public health, whereas in the following years there appeared a slight decreasing tendency in the number of students who chose this subject. It ought to be stressed that majority of the universities included in the study pursue to improve the quality of education according to the recommendations of the Bologna Process. However, alarming is the fact that not all universities take good care of the mobility of their students and employees. Majority of the academic centers perceive the changes introduced by the Bologna Process in higher education system as a positive necessity, at the same time postulating that there is too little information about it in the Polish society in general. Conclusions. Not all institutions implement the guidelines of education towards public health in the same way. Evidence of that can be a varied offer of specializations and a possibility of pursuing students’ training. Majority of universities in which the survey was carried out made the effort to meet the demands of education by creating an organizational body responsible for introduction and implementation of the guidelines of the Bologna Process.